Internet and Distributed Computing Systems 5th International Conference, IDCS 2012, Wuyishan, Fujian, China, November 21-23, 2012. Proceedings - Xiang, Yang.; Pathan, Mukaddim; Tao, Xiaohui; Wang, Hua.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 5th International Conference on Internet and Distributed Computing Systems, IDCS 2012, held in Wuyishan, Fujian, China, in November 2012. The conference was co-located with the 6th International Conference on Network and System Security, NSS 2012. The 22 revised full papers of IDCS 2012 presented were carefully reviewed and selected from 80 submissions. The papers cover the following topics: ad-hoc and sensor networks; internet and Web technologies; network operations and management; information infrastructure; resilience; fault tolerance and availability.
ad-hoc and sensor networks -- internet and Web technologies -- network operations and management -- information infrastructure -- resilience -- fault tolerance and availability.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data protection; Computer software; Information storage and retrieval systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Systems and Data Security; Information Storage and Retrieval; Software Engineering